Ca2+ transmembrane transport enhances oscillatory growth of cancer cell invadopodia - Junbo Zhao; Haochen Zhang; Yuehua Yang; Ruihao Xue; Ze Gong; Hongyuan Jiang (Communications Physics)
Abstract Invadopodia, dynamic cancer cell protrusions, deform and degrade extracellular matrix (ECM) to facilitate invasion. Intracellular calcium ions (Ca2+) are critical second messengers involved in cancer cells migration, proliferation, and apoptosis, but their role in invadopodia dynamics remains unclear. Here, we propose a chemo-mechanical model integrating Ca2+ transmembrane transport, myosin contractility, adhesion dynamics, actin polymerization, and membrane type 1 matrix metalloproteinase (MT1-MMP) hydrolysis. We find that increased invadopodia length elevates membrane tension, activating mechanosensitive channels and raising intracellular Ca2+ levels, aligning with experimental observations. Our model reveals that invadopodia oscillatory and monotonic dynamics are governed by actin polymerization and myosin recruitment, with Ca2+ transport enhancing dynamics via myosin recruitment and reciprocal effects on Ca2+ transport. Furthermore, by incorporating MT1-MMP-mediated ECM degradation in our model, we find that ECM degradation promotes invadopodia extension and elevates Ca2+ levels, which shifts the invadopodia dynamics from monotonic to oscillatory. Overall, our model offers a comprehensive theoretical framework for understanding Ca2+ transport and invadopodia dynamics in cancer cells.